AAIOFI المرابحة للامر لشراء في ظل معايير المحاسبة و المراجعة للمؤسسات المالية الاسلامية - عبدالكريم خيري; د/ امحمد علالي (جامعة عمار ثليجي الاغواط, 2024)
Abstract: This study addresses the topic of Murabaha to the purchase orderer in light of the Sharia standards set by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). The study aims to explore the jurisprudential issues contained within the Sharia standard on Murabaha issued by AAOIFI and to assess its compliance with the procedures, restrictions, and Sharia rulings related to sales in general and Murabaha in particular. He study concluded that the existence of a specific Sharia standard for the Murabaha contract, with clear legal wording, enables financial institutions to follow it with clarity and confidence, ensuring the application of Sharia rulings without ambiguity. Adherence to this standard also helps financial institutions gain the trust and respect of their clients. Furthermore, the study found that the Murabaha standard comprehensively covers its principles, addresses most of its details, and considers the procedures, restrictions, and rulings at all stages. Keywords:Murabaha, Murabaha to the purchase orderer, Sharia standards of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI).